(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
The main objective of this research was to establish the changes occurred after two years of implementation of Sectorial Technical Standard NTS-TS 001 issued by ICONTEC and implemented in the Historic Center of Cartagena with the purpose of improving tourist services and with it the image from the city. The design of the research was descriptive and corresponds to the qualitative type; It was based on the analysis of the current situation of tourism service providers together with the other actors in the production chain, including the academy, based on direct observation, interviews and photographs of the sector. As a result, the tourist destination has more than 120 plans to strengthen the management system for sustainability; 40 Environmental Plans, 50 Sociocultural Plans and 30 Economic Plans, various achievements have been achieved such as compliance with Law 1453 (2011) Penal Code, the Childhood and Adolescence Code, Law 99 (1993) on Environment and the Regulatory Decree of the Environment and Sustainable Development Sector, with the support of the Public Environmental Establishment, the Environmental Police and the Mayor’s Office. It is concluded that the Historic Center of Cartagena has had a favorable impact from the implementation of the norm NTS-TS-001-1 of ICONTEC, both environmental, cultural and inclusion, highlights the closure of the nonconformity reference to the activity of Tourist Cars in the Historical Center and the International Summer School.